Evaluation of aortic valve stenosis using a hybrid approach of Doppler echocardiography and inert gas rebreathing - Hamm, Karsten; Trinkmann, Frederik; Heggemann, Felix; Grüttner, Joachim; Schmid-Bindert, Gerald; Borggrefe, Martin; Haghi, Dariusch; Saur, Joachim (In vivo, 2012)
Background: Doppler echocardiography is the method of choice for diagnosis and evaluation of aortic stenosis. However, there are well-known limitations to this method in difficult-to-image patients. Flow acceleration in the left ventricular outflow tract (LVOT) can lead to overestimation of stroke volume (SV) and poor acoustic windows may impede the exact measurement of the LVOT. The present study aimed to evaluate the use of inert gas rebreathing (IGR)-derived SV in this situation. Patients and Methods: We replaced Doppler-derived SV measurements in the continuity equation (method A) by SV determined by IGR (method B) and by thermodilution during right heart catheterization (method C) to calculate the aortic valve area (AVA) in 21 consecutive patients with moderate or severe aortic stenosis. Results: Mean SV and AVA did not differ between methods at 72±21 ml and 0.71±0.2 cm2 (method A) vs. 66±18 ml and 0.67±0.21 cm2 (method B) vs. 64±15 ml and 0.67±0.21 cm2 (method C), respectively (all p-values >0.05). The mean difference and limits of agreement for AVA were 0.04±0.23 cm2 and -0.40 to 0.47 cm2 between methods A and B, 0.05±0.14 cm2 and -0.26 to 0.27 cm2 between A and C, and -0.05±0.23 cm2 and -0.45 to 0.35 cm2 between B and C, respectively (all p-values >0.05). Conclusion: The presented approach is a reliable method for the calculation of AVA and can add a diagnostic option for the use in difficult-to-image patients. Whereas the use of thermodilution is limited due to its invasive nature, IGR allows the fast and non-invasive determination of cardiac function at low cost.